Angiotensin Receptor Blocker and Neprilysin Inhibitor Suppresses Cardiac Dysfunction by Accelerating Myocardial Angiogenesis in Apolipoprotein E-Knockout Mice Fed a High-Fat Diet - Suematsu, Yasunori; Tashiro, Kohei; Morita, Hidetaka; Ideishi, Akihito; Kuwano, Takashi; Miura, Shin-ichiro (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Hypothesis. Myocardial angiogenesis is important for maintaining cardiac contractile function in patients with cardiac hypertrophy. Evidence shows that angiotensin receptor blocker and neprilysin inhibitors (ARNIs) improve heart failure. The present study investigated the myocardial angiogenic effect of valsartan plus sacubitril in early-stage cardiac dysfunction. Materials and Methods. Male apolipoprotein E-knockout mice fed a high-fat diet were divided into control (CTL), valsartan (30 mg/kg) (VAL), sacubitril (30 mg/kg) (SAC), and valsartan plus sacubitril (30 mg/kg each) (VAL/SAC) groups after 4 weeks of prefeeding and were subsequently treated for 12 weeks. Results. The VAL/SAC group exhibited significantly higher serum brain natriuretic peptide levels; more subtle changes in left ventricular systolic diameter, fractional shortening, and ejection fraction, and significantly higher expression levels of natriuretic peptide precursor B and markers of angiogenesis, including clusters of differentiation 34, vascular endothelial growth factor A, and monocyte chemotactic protein 1, than the CTL group. Conclusions. Valsartan plus sacubitril preserved left ventricular systolic function in apolipoprotein E-knockout mice fed a high-fat diet. This result suggests that myocardial angiogenic factors induced by ARNI might provide cardioprotective effects.